Error analysis of undergraduate students' writing performances: IELTS-based activities - Novrika Nartiningrum; Pusfika Rayuningtya; Diska Fatima Virgiyanti (UIN Raden Mas Said Surakarta, 2021)
As English as a Foreign Language (EFL) students, it is expected that they should have good ability in four skills of English, including writing skill. However, errors are still found in students’ written works. This paper examines the different types of writing errors made by 10 Indonesian undergraduate students who were enrolled in an IELTS preparation class. Descriptive qualitative research was employed in this study. The errors in the term papers were identified and classified accordingly. The students’ works were assessed based on four aspects: task achievement, cohesion and coherence, lexical resource, grammatical range, and accuracy. The result of this study showed that the highest percentage of students’ errors was in terms of lexical resource and grammatical range (accuracy), followed by three other common errors: singular or plural, word choice, and punctuation. Regarding to the task achievement, in Task 1, most of the students addressed the task but they didn't cover all the information needed. While in Task 2, some students presented clear opinions but with limited and inadequately developed ideas and gave no conclusion. Furthermore, for the results of cohesion and coherence in Task 1, most students showed good logical sequence and overall progression but with faulty cohesion devices. However in Task 2, some students presented either incoherent or illogical ideas or information. These results contribute as fruitful insights for language learners who want to enhance the IELTS comprehension, particularly writing performance.